METHODOLOGY FOR DESIGNING HARDWARE AND SOFTWARE FOR SENSORS OF MECHATRONIC MODULES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the methodology for designing hardware and software for sensors of mechatronic modules. It analyzes the purpose and objectives of mechatronics as well as the structural composition for the design of mechatronic devices.